Version 10 (modified by chak, 10 years ago) (diff) |
---|

# Type Checking with Indexed Type Synonyms

## Outline

- Background
- The challenge
- A first (naive) attempt
- A second attempt
- type checking with type functions using local completion
- method can be proven correct by establishing a connection between type function and CHR derivations

## Background

GHC has now FC as its typed intermediate language. In a next step, we wish to add type functions to GHC's source language. Type functions in combination with type annotations and GADTs allow us to type check some interesting programs.

data Zero data Succ n data List a n where Nil :: List a Zero Cons :: a -> List a m -> List a (Succ m) type family Add :: * -> * -> * type instance Add Zero y = y type instance Add (Succ x) y = Succ (Add x y) append :: List a l -> List a m -> List a (Add l m) append Nil xs = xs append (Cons x xs) ys = Cons x (append xs ys)

However, type checking with type functions is challenging.

## The challenge

Consider the axioms

forall a. S [a] = [S a] (R1) T Int = Int (R2)

S and T are type functions of kind *->* For convenience, I drop the `redundant' forall a. on R1's lhs.

Suppose some type annotations/pattern matchings give rise to the local assumptions

T [Int] = S [Int] (R3) T Int = S Int (R4)

and under these assumptions we need to verify

T [Int] = [Int]

Logically, we can express the above as follows:

(forall a. S [a] = [S a]) /\ -- axioms (T Int = Int) |= (T [Int] = S [Int]) /\ -- local assumptions (T Int = S Int) implies (T [Int] = [Int]) -- (local) property

That is, any model (in the first-order sense) which is a model of the axioms and local assumptions is also a model of the property.

NOTE: There are further axioms such as reflexitivity of = etc. We'll leave them our for simplicitiy.

The all important question: How can we algorithmically check the above statement? Roughly, we perform the following two steps.

- Generate the appropriate implication constraint out of the program text. That's easy cause GHC supports now implication constraints. (There are some potential subtleties, see GENERATEIMP below).
- Solve the implication constraint by applying axioms and local assumptions until the (local) property is verified. That's the hard part.

NOTE:

We assume that (implication) constraints consist of equality constraints only. In general, we'll also find type class constraints. We ignore such constraints for the moment.

In the following, we assume that symbols t refer to types and symbols C refer to conjunctions of equality constraints and Ax refers to an axiom set.

We'll restrict ourselves to simple implication constraints of the form ` C implies t1=t2 `
In general, implication constraints may be nested, e.g
` C1 implies (C2 implies C3) ` and may contain conjunctions
of implications, e.g. `C1 implies (F1 /\ F2)` where F1 and F2 are arbitrary implication constraints. Implication constraints may be universally quantified, e.g.
` forall a (S a = T a implies ...) `
These universal quantifiers arise from universal type annotations, e.g. ` f :: S a = T a => ....`, and
pattern matchings over data types with abstract components, e.g. data Foo where
` K :: S a = T a => a -> Foo`
We can operationally deal with universally quantified variables by skolemizing them (and we must ensure that skolemized/universal variables do not escape).

End of NOTE

## A first (naive) attempt

To solve `(C implies t1=t2)` with respect to Ax

- We interpret Ax /\ C as a rewrite system (from left to right).
- We exhaustively apply rewrite rules on t1 and t2, written t1 -->* t1' and t2 -->* t2' and check that t1' and t2' are syntactically equivalent.

Immediately, we find a problem with this solving strategy. Consider our running example.

Rewrite rules

(forall a. S [a] = [S a]) /\ (R1) -- axioms (T Int = Int) (R2) /\ (T [Int] = S [Int]) /\ (R3) -- local assumptions (T Int = S Int) (R4)

applied to `(T [Int] = [Int])`

yields

T [Int] -->* [S Int] (R3,R1) [Int] -->* [Int]

Hence, our (naive) solver fails, but clearly the (local) property (T [Int] = [Int]) holds.

The trouble here is that

- the axiom system Ax is confluent, but
- if we include the local assumptions C, the combined system Ax /\ C is non-confluent (interpreted as a rewrite system)

Possible solutions:

Enforce syntactic conditions such that Ax /\ C is confluent. It's pretty straightforward to enforce that Ax and constraints appearing in type annotations and data types are confluent. The tricky point is that if we combine these constraints they may become non-confluent. For example, imagine

Ax : T Int = Int a= T Int -- from f :: a=T Int => ... implies (a = S Int -- from a GADT pattern implies ...)

The point is that only during type checking we may encounter that Ax /\ C is non-confluent! So, we clearly need a better type checking method.

## A second attempt

To solve `(C implies t1=t2)` with respect to Ax

- First:
- We interpret Ax /\ C as a rewrite system (from left to right) and
- perform completion until the rewrite system is confluent.

- We exhaustively apply rewrite rules on t1 and t2, written t1 -->* t1' and t2 -->* t2' and check that t1' and t2' are syntactically equivalent.

Step (1.1) is new and crucial. For confluent rewrite systems the checking step (2) will work fine (we also need termination of course). But how do we now that completion will succeed? The important condition is to guarantee that Ax is confluent (and terminating) then completion will be successful (i.e. terminated and produce a confluent rewrite system).

Let's take a look at our running example.

(forall a. S [a] = [S a]) /\ (R1) -- axioms (T Int = Int) (R2) /\ (T [Int] = S [Int]) /\ (R3) -- local assumptions (T Int = S Int) (R4)

The axioms are clearly confluent but there's a critical pair between (R2,R4).

Completion yields

(S Int = Int) (R5)

Now, we can verify that (T [Int] = [Int])

by executing

T [Int] -->* [Int] (R3,R1,R5) [Int] -->* [Int]

The completion method in more detail.

### There are two kinds of critical pairs

- Axiom vs local assumption, see (R2,R4) above
- Local assumption vs local assumption. For example,
T Int = S Int /\ T Int = R Int

Completion yieldsS Int = R Int R Int = S Int

NOTE: Axiom vs axiom impossible cause axiom set is confluent

Towards establishing a connection between completion and CHR derivation steps

NOTE:

There's a straightforward translation from type functions to constraints. For each n-ary function symbol T, we introduce a n+1-ary constraint symbol T. Thus, we can represent
`T Int = Int` as
` T Int a /\ a=Int`
For example, `T Int = S Int` is represented by
`T Int a /\ S Int b /\ a=b`

We can verify that the completion method success by showing that each critical pair arises in the `corresponding' CHR derivation (this derivation terminates if the axiom system is confluent and terminating, hence, we'll only encounter a finite number of critical pairs, hence, completion terminates).

Recall the critical pair (axioms vs local assumption) from above

T Int = Int -- axiom T Int = S Int -- local assumption

In the CHR world, we'll represent both as

T Int a <==> a=Int -- axiom turned into CHR T Int b /\ S Int c /\ b=c -- local assumption turned into CHR -- constraints

In the CHR world, we find that

T Int b /\ S Int c /\ b=c --> b=Int /\ S Int c /\ b=c -- apply CHR <--> b=Int /\ c=Int /\ S Int Int -- equivalence transformation -- apply mgu

directly corresponds to

S Int = Int

generated by our completion method

Recall the critical pair (local assumption vs local assumption)

T Int = S Int /\ T Int = R Int

represented in the CHR world as

T Int a /\ S Int b /\ a=b /\ T Int c /\ R Int d /\ c=d

In the CHR world, we find that

T Int a /\ S Int b /\ a=b /\ T Int c /\ R Int d /\ c=d -->T Int a /\ S Int b /\ a=b /\ c=a /\ R Int d /\ c=d -- apply FD rule -- T a b /\ T a c ==> b=c <--> T Int a /\ S Int a /\ R Int a /\ a=b, c=a, d=a

directly corresponds to

S Int = R Int R Int = S Int

The general cases are as follows.

#### axiom vs local assumption case

forall as. (T t1 ... tn = s) -- axiom T t1' ... tn' = s' -- local assumption

where exist phi, dom(phi)=as such that phi(ti) = ti' for i=1,...,n

completion yields

s' = phi(s) phi(s) = s'

NOTE: We may need both orientation see above example. We assume that symbol t refers to types NOT containing type functions and s refers to types which may contain type functions (can be lifted, more below)

Explaining completion in terms of CHRs. Above translates to

T t1 ... tn b <==> C T t1' ... tn' b' /\ C'

where s is translated to (C | b) and s' is translated to (C | b')

(see above where each type function type is represented by a variable under some CHR constraints)

The type functions

s' = phi(s) phi(s) = s'

resulting from completion 'appear' in the CHR derivation (i.e. the operational effect is the same)

T t1' ... tn' b' /\ C' -- apply CHR --> b=b', phi(C) /\ C'

#### local assumption vs local assumption

T t1 ... tn = s1 T t1 ....tn = sn

completion yields

s1 = s2 s2 = s1

In the CHR world, above represented by

T t1 ... tn a /\ C1 T t1 ....tn b /\ C2

where s1 translated to (C1 | a)

s2 translated to (C1 | n)

Then,

T t1 ... tn a /\ C1 /\ T t1 ....tn b /\ C2 --> FD rule step T t1 ... tn a /\ C1 /\ a=b /\ [a/b] C2

Again, the operational effect of the type function generated is also present in the CHR derivation

Lifting the restriction that t refers to types NOT containing type functions (we only lift this restriction for local assumptions).

Consider

forall a. T [a] = [T a] -- axiom T [S Int] = s -- local assumption

We can normalize

T [S Int] = s

to

T [b] = s S Int = b

Method from above applies then.

NOTE: Regarding generation of implication constraints. GENERATEIMP

The literate implication constraints generated out of the program text may look as follows

a=T Int implies ( a= S Int implies ...)

The above can be simplified to

(a=T Int /\ a = S Int) implies ...

Before we proceed with the completion method, we first need to apply some closure rules (eg. transitivity, left, right etc) Hence, from the above we generatet

a=T Int /\ a = S Int /\ T Int = a /\ S Int = a /\ -- symmetry T Int = S Int /\ S Int = T Int -- transitivity

We omit the trival (reflexive) equations

T Int = T Int /\ S Int = S Int